Analisis Implementasi Program Promosi Kesehatan di Rumah Sakit Umum Daerah Reda Bolo Kabupaten Sumba Barat Daya - Wole, Bewa Dangu; Santosa, Didik Hadi (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2025)
The provision of healthcare services is increasingly focused on health promotion, maintenance, and protection, rather than solely on disease recovery or treatment. However, in practice, many hospitals still emphasize curative and rehabilitative services due to the suboptimal implementation of Hospital Health Promotion (PKRS). This study aims to analyze the implementation of the PKRS program at Reda Bolo Regional Public Hospital (RSUD) in Southwest Sumba Regency, based on three standards: policy, assessment, and intervention. The study was conducted from February to March 2025 using a descriptive qualitative approach to examine and analyze the implementation of the PKRS program. Data were collected through observation and in-depth interviews. The results indicate that the regulatory aspect of PKRS at RSUD Reda Bolo meets the established standards; however, the assessment and intervention components have not been implemented effectively. Furthermore, health promotion activities are not yet prioritized and are limited to within the hospital environment. Therefore, it is recommended that RSUD Reda Bolo increase the number of PKRS personnel according to organizational structure needs and provide relevant training to enhance human resource competencies in supporting the successful and sustainable implementation of the PKRS program.